Bacterial complement escape. - Jongerius, I; Ram, S; Rooijakkers, S (2009)
Complement activation is a crucial step in our innate immune defense against invading bacteria. Complement proteins can quickly recognize invading bacteria and subsequently label them for phagocytosis or kill them by direct lysis. In order to survive in the human host, bacterial pathogens have evolved a number of excreted and membrane-bound proteins that interfere with several steps of the complement cascade. In this chapter we summarize the most successful complement-modulating strategies by human bacterial pathogens.